Existence: Semantics and Syntax - Comorovski, Ileana; Heusinger, Klaus; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This collection is an important contribution to the semantic and syntactic analysis of the expression of existence. The volume focuses on the three main linguistic constructions expressing existence: copular clauses, existential sentences, and (in)definiteness. The papers analyze the interaction between the basic notion of existence and pervasive phenomena of natural language, such as quantification and presupposition. The contributions represent state of the art research on theoretical and comparative issues related to the expression of existence, and make extensive reference to the semantic and syntactic facts of English and of various other languages. The richness of new data and the juxtaposition of different theoretical stances bring a number of new questions into focus.
The Interpretation of the Copula -- Towards a Dynamic Account of BE in English -- Constituent Questions and the Copula of Specification -- Predication and Equation in Copular Sentences: Russian vs. English -- On Davidsonian and Kimian States -- Existential Sentences Across Languages -- Focus and the Basic Function of Chinese Existential You-Sentences -- Existential Sentences, BE, and the Genitive of Negation in Russian -- Negative Quantification and Existential Sentences -- Existence and the Interpretation of Noun Phrases -- Existence, Maximality, and the Semantics of Numeral Modifiers -- Existential Import -- Referentially Anchored Indefinites -- On Singular Existential Quantifiers in Italian.
Keywords: LINGUISTICS; LINGUISTICS -- PHILOSOPHY; COMPARATIVE LINGUISTICS; ROMANCE LANGUAGES; SEMANTICS; GRAMMAR, COMPARATIVE AND GENERAL -- SYNTAX; LINGUISTICS; SEMANTICS; SYNTAX; PHILOSOPHY OF LANGUAGE; COMPARATIVE LINGUISTICS; ROMANCE LANGUAGES